Single Case Study on Nadi Vrana (Pilonidal Sinus) with Yashtimadhu Ghrita Varti along with Triphala Guggulu. - Basak, Nabanita; Sharma, Vishnu Dutt (International Research Journal of Ayurveda & Yoga, 2023)
Nadi Vrana, also known as Pilonidal sinus is a frequent illness in tropical regions. Nadi Vrana is linked to the occurrence of several cavities or recesses in an ulcer that has a path that extends into the deeper tissues. Nadi Vrana is synonymous with Gati.Gati is the term used to describe conditions where there is an extensive infiltration of pus, due to unsanitary conditions. Despite the enormous advancements made in the field of modern surgery, it is still a difficult and problematic condition. According to the clinical approach taken by contemporary surgeons, Nadi Vrana has been treated incorrectly, ineffectively, with post operative problems and complaints of recurrences in the majority of cases. In this case study, the patient of Nadi vrana is treated with yashtimadhu ghrita varti along with triphala guggulu. After four weeks of observation, the symptoms of Nadi vrana (Pilonidal sinus) has been reduced markedly.